Developing an integrated brand activation strategy framework for platform-dependent creative studios based on the kemsgraphics case - Kusumasari, Adita Ayu; Albaari Kemal, Ammar Muqsith (International Journal of Visual and Performing Arts, 2025)
Digital creative enterprises face significant strategic risk from platform dependency, as reliance on a single marketplace can lead to unstable revenue when algorithmic changes reduce visibility. This research addresses that risk by designing and empirically testing a brand activation strategy to elevate brand awareness for Kemsgraphics, a virtual studio highly dependent on Fiverr. The strategy was developed using the Brand Activation Process (Discovery, Strategic Development, Creative Development, Delivery, and Evaluation) as the primary framework, enriched by the incorporation of the Steps of Effective Communication Development for strategic planning and Design Thinking principles for creative solution development. The impact of the strategy was tested using a quasi-experimental, time-series design with mixed-method analysis, collecting daily performance data and qualitative insights from five digital platforms. The intervention produced an 890% increase in TikTok follower growth and substantial improvements in reach, engagement, and profile visits across all platforms during a five-day period. This research demonstrates how an integrated, theory-based brand activation strategy can help remote creative businesses build brand resilience and reduce platform risk, providing a practical blueprint for managing digital brand presence in the creative sector.